1998
DOI: 10.1046/j.1365-2044.1998.00268.x
|View full text |Cite
|
Sign up to set email alerts
|

How would patients prefer to spend the waiting time before their operations?

Abstract: SummaryMany surgical patients are anxious while waiting to go to the operating theatre in spite of the best preparation with drugs, information and reassurance. It is possible that patients could be more comfortable if allowed a choice of activities before operations. The objective of this study was to find out how pre-operative patients might prefer to occupy their time. We distributed 200 questionnaires to elective surgery patients and 184 (92%) were available for analysis. Of the respondents, 54.1% wanted t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 16 publications
(17 reference statements)
2
7
0
Order By: Relevance
“…However, some references do not coincide with the above study. [2526] These figures may be similar to those found in the study by Hyde et al .,[22] who reported that many patients (two-third) do not prefer to watch the operation. However, our study was not meant to show only procedures of operations but also involved questionnaire of assurance to allay anxiety of the patient.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…However, some references do not coincide with the above study. [2526] These figures may be similar to those found in the study by Hyde et al .,[22] who reported that many patients (two-third) do not prefer to watch the operation. However, our study was not meant to show only procedures of operations but also involved questionnaire of assurance to allay anxiety of the patient.…”
Section: Resultssupporting
confidence: 87%
“…Seeing the patient well in advance as supposed to keeping them uniformed and then 1 h before surgery giving them all the information and asking them to decide, adequate explanation of the benefits, and risks along with the constant communication and reassurance throughout the procedure would establish rapport, build confidence, trust, and alleviate all fears. [22] Different methods have been used to reduce patient's anxiety such as giving sedatives or advising patients to listen to music of their preferences either preoperatively or during the operation. However, our study devised the method of showing video clipping/images[2324] of various patients going to surgery from PAC room to operation table showing the particular clipping of a specific operation to the patient undergoing some procedure, using questionnaire method devised by the HAM-A scale.…”
Section: Resultsmentioning
confidence: 99%
“…This may have added to the controversy regarding the efficiency of these methods,25,26 and the availability of these educational materials in our hospitals. These figures may be similar to those found in a study by Hyde et al23 who reported more than two thirds of patients preferred not to watch the operation.…”
Section: Discussionsupporting
confidence: 91%
“…All of these measures are well established methods to reduce patients’ anxiety,9,10 and patients usually gain benefit from them 23. Several respondents commented upon the effectiveness of using anatomy slides and an orthopedic spine model to demonstrate how/where spinal/epidural needles are inserted, emphasizing they do not go into the cord itself.…”
Section: Discussionmentioning
confidence: 99%
“…Some researchers have found that in the waiting room area of an operation theatre, both head phone and broadcast music was effective in reducing the preoperative anxiety (Hyde et al, 1998). Music therapy pre-operatively reduces post-operative pain and analgesic requirements.…”
Section: Perioperative Settingmentioning
confidence: 99%